1997
DOI: 10.1063/1.365126
|View full text |Cite
|
Sign up to set email alerts
|

Band metamagnetism and related phenomena in Er(Co1−xSix)2

Abstract: We report on magnetic, transport, and cohesive properties of Er(Co1−xSix)2 compounds in varying external conditions (T,H,p). The localized Er 4f magnetic moments in ErCo2 order ferromagnetically below TC=33 K. The Co 3d band states form no moment above TC, but below TC the majority and minority 3d sub-bands split due to strong 4f−3d exchange interaction. Consequently, Co moments of ∼1 μB appear coupled antiparallel to the Er moments. This is accompanied by a ∼50% resistivity drop and an abrupt lattice expansio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…The compounds selected for the study are DyCo 2 and Er(Co 1-x Si x ) 2 [x= 0, 0.025 and 0.05]. Though the pressure dependence of magnetic and electrical properties have been studied in RCo 2 compounds [19][20][21][22][23] , to the best of our knowledge this is the first report on the influence of pressure on the MCE in parent as well as substituted RCo 2 compounds. Furthermore, probably for the first time, a thermodynamic analysis based on the Landau theory of phase transitions has been carried out to study the change in the order of magnetic transition in these compounds under nonmagnetic substitution as well as applied pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The compounds selected for the study are DyCo 2 and Er(Co 1-x Si x ) 2 [x= 0, 0.025 and 0.05]. Though the pressure dependence of magnetic and electrical properties have been studied in RCo 2 compounds [19][20][21][22][23] , to the best of our knowledge this is the first report on the influence of pressure on the MCE in parent as well as substituted RCo 2 compounds. Furthermore, probably for the first time, a thermodynamic analysis based on the Landau theory of phase transitions has been carried out to study the change in the order of magnetic transition in these compounds under nonmagnetic substitution as well as applied pressure.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, detailed comparative measurements of the transport and magnetic properties of the ErCo 2 have shown that the resistivity drops at a temperature which is somewhat (ϳ1 K) lower than T C marked by the diverging susceptibility. 9 This result has supposed that the onset of the cobalt magnetism appears at T 0 ϳ(T C Ϫ1) K. It has also been found in the Er 0.55 Y 0.45 Co 2 that the difference between the temperature at which magnetic neutron scattering disappears and the temperature of the sharp drop in resistivity attains ϳ6 K. 5 However, authors concluded that different values of T C obtained by different methods are caused by the inhomogeneous and complicated magnetic structure of the compounds near x c . Recently, it has been suggested that in R 1Ϫx Y x Co 2 in a limited concentration range around x c a separate ordering of the two magnetic sublattices can be anticipated.…”
mentioning
confidence: 99%
“…The former five samples were found to crystallize in the same MgCu 2 -type (C15) structure as ErCo 2 . The single-phase materials (for comparison also samples ErCo 2 and Er(Co 0.95 Si 0.05 ) 2 from previous studies [2] have been included) were studied by the magnetization, electrical resistivity, thermal expansion (by X-ray diffraction and strain-gauge methods with miniature strain gauges from Micro-Measurements and Kyowa) and specific heat experiments with respect to temperature and magnetic field dependency. Majority of reported measurements were performed using the PPMS 9T apparatus (Quantum Design) in the JLMS, Prague.…”
Section: Methodsmentioning
confidence: 99%